G348(P) I can't say that to a twelve year old. (May 2019) - Walsh, H; Iverson, M; Harris, S
Abstract : Aim: To determine the effectiveness of adding a HEADSSS screening assessment tool to the admissions unit clerking proforma in improving adolescent psychosocial assessment. Method: An initial audit carried out on the basic psychosocial health assessment of adolescents showed poor compliance. An additional 'S' was added to the HEADSS tool, to explore any concerns young people may have with social media. The HEADSSS (Home, Education, Activities, Drugs, Social media, Suicide, Sexuality) screening tool was subsequently incorporated into the paediatric admissions clerking proforma. This was accompanied by informal teaching sessions, a guideline on use and specific referral pathways should a risk factor be identified. Qualitative information was also gathered about the adolescents' perception at being asked these screening questions and clinicians responses to using the tool. Results: The initial audit showed that clinicians are persistently poor at assessing the psychosocial wellbeing of adolescents admitted to the paediatric ward. The worst areas of performance being assessment of alcohol/drug use and sexual health. A re-audit after implementation of the HEADSSSS screening tool and guidelines, showed a marked improvement in these results but there remains significant hesitancy from clinicians to ask the screening questions. Conclusion: Our study showed improved compliance when the HEADSSS tool is incorporated into the admission documentation. Clinicians need ongoing encouragement to overcome their hesitancy to ask some questions. Admission to the paediatric assessment unit is an opportune time to identify at risk adolescents and signpost to appropriate intervention.